TIPIOLOGI PEMIMPIN DALAM ORGANISASI DEMI TERCAPAINYA VISI MISI ORGANISASI - Erwin Syahputra; Dewi Sartika; Deliyaman Giawa; Renita Dewi; Sri Ramayani; Kamila Ainun (Nusantara Hasana Journal, 2022)
Leadership is closely related to a person's skills, abilities and knowledge in terms of influencing others to do something that is the desire and goal of a leader. A leader must have different types or traits, so with the typology of leadership, each type or nature of each leader can be grouped so that harmony is created between the leader's relationship with its members, these attitudes and behaviors can be formed and influenced by several things such as background. family background, education level, social environment, personal interests and organizational interests so as to achieve the vision and mission of the organization.